2015
DOI: 10.1038/srep14014
|View full text |Cite
|
Sign up to set email alerts
|

Punicalagin, an active component in pomegranate, ameliorates cardiac mitochondrial impairment in obese rats via AMPK activation

Abstract: Obesity is associated with an increasing prevalence of cardiovascular diseases and metabolic syndrome. It is of paramount importance to reduce obesity-associated cardiac dysfunction and impaired energy metabolism. In this study, the activation of the AMP-activated protein kinase (AMPK) pathway by punicalagin (PU), a major ellagitannin in pomegranate was investigated in the heart of a rat obesity model. In male SD rats, eight-week administration of 150 mg/kg pomegranate extract (PE) containing 40% punicalagin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 49 publications
3
63
0
Order By: Relevance
“…Visceral fat obesity is often associated with increased risk for diseases such as atherosclerosis, dyslipidemia, hypertension, cerebrovascular thrombosis, diabetes and ischemic heart disease234. Particularly in the heart, obesity has a strong impact on left ventricle hypertrophy, myocardial fibrosis and atrial fibrillation that eventually leads to heart failure5.…”
mentioning
confidence: 99%
“…Visceral fat obesity is often associated with increased risk for diseases such as atherosclerosis, dyslipidemia, hypertension, cerebrovascular thrombosis, diabetes and ischemic heart disease234. Particularly in the heart, obesity has a strong impact on left ventricle hypertrophy, myocardial fibrosis and atrial fibrillation that eventually leads to heart failure5.…”
mentioning
confidence: 99%
“…Previous studies have shown that PUN exerts considerable antioxidant properties in lipopolysaccharide-induced macrophages and exhibits neuroprotective effects against cerebral ischemia-reperfusion insult via its anti-oxidant potential (Yaidikar et al, 2014). Moreover, it is reported that PUN prevents high-fat diet-induced cardiac metabolic disorders (Cao et al, 2015). These studies suggested PUN may provide cardioprotection against MI/R injury via anti-oxidant action.…”
Section: Introductionmentioning
confidence: 70%
“…Punicalagin (PUN) is widely recognized as the major active compound in pomegranate juice, which exerted beneficial anti-oxidative effects similar to pomegranate juice (Chen et al, 2012;Zou et al, 2014). Attractively, recent studies showed that PUN treatment attenuated cerebral ischemia reperfusion-induced oxidative brain injury (Yaidikar et al, 2014) and prevented cardiac metabolic disorders in high-fat diet-fed rats (Cao et al, 2015). These studies suggest that PUN may exert protective effects on MI/R injury.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations